Molecular docking of secondary metabolites from Indonesian marine and terrestrial organisms targeting SARS-CoV-2 ACE-2, M pro, and PL pro receptors - Gita Syahputra; Nunik Gustini; Bustanussalam Bustanussalam; Yatri Hapsari; Martha Sari; Ardi Ardiansyah; Asep Bayu; Masteria Yunovilsa Putra (Pensoft Publishers, 2021)
With the uncontrolled spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), development and distribution of antiviral drugs and vaccines have gained tremendous importance. This study focused on two viral proteases namely main protease (Mpro) and papain-like protease (PLpro) and human angiotensin-converting enzyme (ACE-2) to identify which of these are essential for viral replication. We screened 102 secondary metabolites against SARS-CoV-2 isolated from 36 terrestrial plants and 36 marine organisms from Indonesian biodiversity. These organisms are typically presumed to have antiviral effects, and some of them have been used as an immunomodulatory activity in traditional medicine. For the molecular docking procedure to obtain Gibbs free energy value (∆G), toxicity, ADME and Lipinski, AutoDock Vina was used. In this study, five secondary metabolites, namely corilagin, dieckol, phlorofucofuroeckol A, proanthocyanidins, and isovitexin, were found to inhibit ACE-2, Mpro, and PLpro receptors in SARS-CoV-2, with a high affinity to the same sites of ptilidepsin, remdesivir, and chloroquine as the control molecules. This study was delimited to molecular docking without any validation by simulations concerned with molecular dynamics. The interactions with two viral proteases and human ACE-2 may play a key role in developing antiviral drugs for five active compounds. In future, we intend to investigate antiviral drugs and the mechanisms of action by in vitro study.